Information, consequentiality and credibility in stated preference surveys: A choice experiment on climate adaptation - Malte Welling; Ewa Zawojska; Julian Sagebiel (ZBW - Leibniz Information Centre for Economics, 2021)
Information provided in valuation surveys has been shown to affect stated preferences, which in turn may matter for the validity and reliability of survey-based value estimates. Although such information effects are widely documented, the reasons underlying the effects are less established. We examine two pathways which might explain information effects in stated preferences, using additional information about a climate adaptation strategy as an experimental treatment in a choice experiment on nature based climate adaptation measures in the German city of Bremen. We hypothesize and empirically analyze whether information effects can emerge as a result of changed perceptions (1) about the credibility of the scenario and (2) about the survey consequentiality upon facing additional information. We find that the additional information strengthens perceived credibility of the scenario and strong credibility perceptions increase value estimates. In our study, the role of the information on consequentiality perceptions appears to be negligible.
Keywords: Q51; 330; environmental valuation; discrete choice experiment; information effects; perceivedconsequentiality; perceived credibility; urban ecosystem services ·